Microencapsulation of Lactobacillus plantarum in Lactic Acid Fermentation of Winter Melon (Benincasa hispida) Juice - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
Winter melon (Benincasa hispida) is a popular vegetable that were grown primarily for its use as a vegetable and usually recognized for its nutritional and medicinal properties. Consumers tend to prefer the food and beverages that are fresh, highly nutritional, health promoting and ready to consume. Objective of this study focused on different technical parameters such as the initial soluble solid content (6.0, 6.5, 7.0, 7.5, 8.0 oBrix), loading ratio of Lactobacillus plantarum encapsulated in calcium alginate bead (2.0, 4.0, 6.0, 8.0 10.0 g/100mL), fructo-oligosacharide (0.5%, 1.0%, 1.5%, 2.0%, 2.5%) as prebiotic affecting to the lactic acid fermentation of winter melon juice. Results showed that the best quality of the fermented winter melon juice would be achieved by the initial soluble solid content of juice 7.5 oBrix, Lactobacillus plantarum bead loading 8.0 g/100mL, fructo-oligosacharide 2.0%. Through fermentation, winter melon juice was preserved and maintained, while improving the nutritive and sensory properties. Lactobacillus plantarum was stable under acidic condition by the microencapsulation. The probiotic winter melon juice is very beneficial for health as health it plays an important role in immune system improvement.Keywords: Benincasa hispida, Lactobacillus plantarum, Microencapsulation, Fermentation, Fructo-oligosacharide, Juice.